Inseminação artificial em tempo fixo em primíparas nelore lactantes acíclicas - Cunha, Rodrigo Ribeiro (2011)
The objective of this experiment was to evaluate the efficiency of a Fixed Time Artificial Insemination (TAI) protocol in an attempt to improve the reproductive performance of primiparous lactating acyclic Nelore cows. The experiment was conducted for a period of breeding season (BS) of 180 days. Were used 350 Nelore cows with body condition score (BCS) greater than 2.5 (average 2.65 ± 0.01) and days postpartum average of 67.35 ± 1.0 days. The animals were divided into four groups: G1 (n = 61) and G3 (n = 116) - cows with ovarian follicles smaller than 8mm in diameter and absence of CL. G2 (n = 57) and G4 (n = 116) - cows with follicles greater than 8mm and absence of CL. G1 and G2 remained with the bulls in the management of natural mating (NM) throughout the experimental period, from day 0 of BS. The G3 and G4 were treated (Day 0) with an intravaginal device containing 1.0 g of P4 for 8 days and 2mg (2ml) of estradiol benzoate (EB) IM. The withdrawal of P4 (Day 8) were applied IM 400 IU (2ml) of eCG and 75μg (2ml) of cloprostenol and 24 hours later (Day 9), administered 1mg (1ml) IM BE. The TAI was performed between 51-54 hours after withdrawal of P4 (Day 10) using semen from a single bull. After five days of the TAI, cows in groups G3 and G4 were submitted with bulls in the management of NM. All animals were evaluated by ultrasound for cyclicity rates (presence of CL) and pregnancy diagnosis at 45 and 210 days after onset of BS. For the analysis of the presence of CL and pregnancy rates at 45 and 210 days, between groups, were performed a chi-square. For the variable: period of service was used ANOVA and Duncan. At 45 days of BS, the G3 (42.24% A) and G4 (51.70%) presented higher rates of pregnancy (P <0.05) than G1 (0% B) and G2 (3 5% B). A greater number of ovulations was also found (P <0.05) in G3 and G4 when compared to animals maintained only during NM (6.56% C, 28.07% B 50.86% A, 62, 93%, for G1, G2, G3 and G4, respectively). Pregnancy rates at 210 days were: 22.95% C (G1), 45.61% B (G2), 40.51% B (G3) and 65.51% A (G4). For percentage of animals with CL at 180 days of MS, the G4 (71.55% A) obtained better results than Groups 1, 2 and 3 (42.62% B 56.14% B 48.27% B, respectively). Additionally, groups of TAI + eCG had shorter periods of service (days, P <0.05): G1 (134.00 ± 11.70 A), G2 (119.65 ± 8.27 A), G3 (79, 91 ± 5.38 B) and G4 (81.40 ± 4.59 B). The work suggests that the TAI was effective to improve the reproductive efficiency of primiparous lactating acyclic Nelore cows in compared to females subjected only NM. In addition, primiparous cows subjected to TAI at the beginning of BS had the reduced postpartum anoestrus period and increased pregnancy rates than cows subjected only to NM.